Greatly Enhanced Resonant Exciton-Trion Conversion in Electrically Modulated Atomically Thin WS2 at Room Temperature - Wang, Zeng (Advanced materials (Deerfield Beach, Fla.), 2023)
© 2023 Wiley-VCH GmbH.